Ethno-medicinal survey of important plants practiced by indigenous community at Ladha subdivision, South Waziristan agency, Pakistan. Issue 1 (December 2016) - Aziz, Muhammad; Adnan, Muhammad; Khan, Amir; Rehman, Atiq; Jan, Rahmatullah; Khan, Jafar
Abstract Background Medicinal flora plays a vital role in treating various types of ailments in living beings. The present study was planned to investigate and document systematically the indigenous knowledge in a scientifically little explored area of Ladha sub-division, South Waziristan agency, Pakistan. Hence, this study would contribute positively to the field of ethnopharmacology. Methods Prior to ethnomedicinal data collection, regular field visits were conducted during the month of May and June 2015 to locate the sites and respondents from where the traditional knowledge was to be recorded. Ethno-medicinal data was collected during the month July and August 2015 through rapid appraisal approach (RAA) based on direct interaction with the indigenous communities by making group discussions, corner meetings and semi-structured interviews. Data was evaluated statistically by using the index of Use value (UV) and Frequency of citations (FC). Results A total of 82 medicinal plants belonging to 42 families were reported in the study. Leaves were the most frequently used plant parts. Highest use values were recorded forPeganum harmala (0.93), Punica granatum (0.91), Thymus mongolicus (0.90), Chenopodium album (0.89), Coriandrum sativum (0.87), Mentha longifolia (0.87), Lactuca serriola (0.87) andPortulaca oleracea (0.87). Medicinal plants used for the gastro intestinal complexities and respiratory diseases were more than 9% followed by skin and diarrhea (7% each), liver disorders (5%) cough and cold fever (5%). Conclusion People of the area mostly still rely on traditional herbal therapies. Keeping in mind the dependence of the indigenous community for their primary health care on such herbal remedies, pharmacological and critical toxicological investigation of certain flora is necessary. Moreover, projects should be designed to analyze the existing issues and problems related with medicinal plants conservation.